Patterns of spatial distribution and behaviour of fish on a rocky intertidal platform at high tide - Faria, Cláudia Barreiros Macedo de (2012)
We describe the patterns of spatial distribution and behaviour of an intertidal fish assemblage on a rocky intertidal platform in the south of Portugal during high tide. Data were collected by surveying a number of predefined transects and focal observations of individual fish. Several interspecific differences, in both zonation and substratum, were found at high tide that were not apparent in observations of pools at low tide. Parablennius sanguinolentus occurred mainly on boulders at the high intertidal, Lipophrys pholis and Coryphoblennius galerita were especially abundant in the upper intertidal. L. canevae and L. trigloides were most abundant in the low intertidal, with L. canevae being restricted to that level. Gobius cobitis used all shore levels, including a significant presence in the subtidal. Species typically considered subtidal, like P. pilicornis and P. gattorugine, were found also in the intertidal at high tide. In the case of P. gattorugine both juveniles and even large adults moved up with the tide, reaching the highest shore levels. C. galerita seemed to be restricted to the vicinity of its low-tide shelters, around crevices and pools, while large specimens of L. pholis and G. cobitis were subject to larger displacements, up and down with the tide. Apart from the benthic component, the fish assemblage is enriched at high tide by a large number of fish, mainly juveniles of pelagic and bentho-pelagic species, meaning that the rocky intertidal may play a nursery role for several non-resident fish species.